Filterless Visible-Range Color Sensing and Wavelength-Selective Photodetection Based on Barium/Nickel Codoped Bandgap-Engineered Potassium Sodium Niobate Ferroelectric Ceramics - Balanov, Vasilii A.; Temerov, Filipp; Pankratov, Vladimir; Cao, Wei; Bai, Yang (Wiley-Blackwell, 2023)
Photosensors, photodetectors, or color sensors are key components for various optical and optoelectronic applications. Semiconductor-based photodetection has been a dominator which is excellent at measuring the photon intensity of incident light. However, the wavelength of the incident light to be measured must be known beforehand and it mostly depends on auxiliary methods to filter unknown wavelengths. Herein, an alternative but simple mechanism that is using a monolithic, bandgap-engineered photoferroelectric ceramic to blindly determine the wavelength and intensity of incident light at the same time is demonstrated. The photoferroelectric compound is Ba- and Ni-codoped (K,Na)NbO3 exhibiting a direct bandgap of ≈2 eV and a spontaneous polarization of ≈0.25 C m−2. The band–band charge carrier transition is confirmed by multiple characterization methods of photoluminescence, photodielectric spectroscopy, and photoconductivity. The existent optoelectrical cumulative effect enabled by the simultaneous narrow bandgap and strong ferroelectricity allows to reliably distinguish the wavelengths of 405, 552, and 660 nm as well as the power density ranging from ≈0.1 to 10 W cm−2, with the photoresponsivity of up to 60 μA W−1. Consequently, this work proposes an alternative to semiconductor-based counterparts for filterless, wavelength-selective photodetection and color sensing. © 2022 The Authors. Solar RRL published by Wiley-VCH GmbH. --//-- Balanov V.A., Temerov F., Pankratov V., Cao W., Bai Y., Filterless Visible-Range Color Sensing and Wavelength-Selective Photodetection Based on Barium/Nickel Codoped Bandgap-Engineered Potassium Sodium Niobate Ferroelectric Ceramics (2023) Solar RRL, 7 (3), art. no. 2200995, DOI: 10.1002/solr.202200995, https://www.scopus.com/inward/record.uri?eid=2-s2.0-85142936298&doi=10.1002%2fsolr.202200995&partnerID=40&md5=9af5e9b9c683edd409a7a1b15439782e published under the
This work was supported by University of Oulu and the European Research Council (ERC) under the ERC Starting Grant (agreement number 101039110). V.B. acknowledges the EDUFI Fellowship provided by the Finnish National Agency for Education. F.T. and W.C. acknowledge financial support from the European Research Council (ERC) under the European Union’s Horizon 2020 research and innovation programme (grant agreement no. 101002219). The Institute of Solid State Physics, University of Latvia as the Center of Excellence, has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement no. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES; KNBNNO; perovskites; photodielectrics; photoferroelectrics; photoluminescence; photosensors